2015
DOI: 10.1007/s13277-015-4383-1
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-activated miR-144 regulates autophagic survival of prostate cancer cells against Cisplatin

Abstract: Cisplatin is a commonly used chemotherapy drug for prostate cancer (PC). However, some PCs are resistant to cisplatin treatment, while the molecular mechanisms underlying the resistance of PCs to cisplatin are not completely understood. In this study, we found that cisplatin dose-dependently activated Beclin-1 in two PC cell lines, PC3 and LNCap. Autophagy suppression significantly increased the cisplatin-induced cell death of these PC cells in a CCK-8 assay. Moreover, microRNA (miR)-144 levels were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 50 publications
3
17
0
Order By: Relevance
“…Although the tumor suppressive effects of miR‐124 and miR‐144 were reported in previous studies , whether their expression was altered in hypoxia has not been reported yet. In this study, we observed that miR‐124 and miR‐144 were significantly downregulated in hypoxia, which might be a result of impaired Dicer expression.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although the tumor suppressive effects of miR‐124 and miR‐144 were reported in previous studies , whether their expression was altered in hypoxia has not been reported yet. In this study, we observed that miR‐124 and miR‐144 were significantly downregulated in hypoxia, which might be a result of impaired Dicer expression.…”
Section: Discussionmentioning
confidence: 89%
“…A and B). MiR‐124 and miR‐144 are two tumor suppressors of prostate cancer . The microarray analysis showed these two miRNAs were decreased dramatically in hypoxia in both DU145 and PC3 cells (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Another study confirmed that the expression levels of sputum and serum miR-144-3p were significantly upregulated in the tuberculosis patients, but were found to decrease significantly after anti-tuberculosis treatment [26]. In addition, it has been reported that cisplatin-induced VEGF can suppress the expression levels of miR-144 in prostate cancer cells, which subsequently upregulates Beclin-1 to increase autophagic cell survival against cisplatin-induced cell death [27]. Chen S et al have shown that miR-144 increased autophagy in lung cancer cells by targeting TIGAR [28].…”
Section: Introductionmentioning
confidence: 92%
“…In terms of chemoresistance, miR-144 reversed 5-FU and imatinib resistance respectively in HCC (461) and leukemia (462). In addition, miR-144 might promote cisplatin sensitivity in prostate cancer (463) and in thyroid carcinoma (464). Whereas miR-144-3p contributed to sunitinib resistance in RCC by targeting ARID1A, a cancer gene involved in chromatin remodeling (465).…”
Section: Drugs/non-coding Rnas Subnetworkmentioning
confidence: 99%